Ichnofossils of the Permian-Triassic Sediments in the Southern Verkhoyansk Region (Tiryakh-Kobyume Section, Republic of Sakha (Yakutia), Russia) - Miftakhutdinova D.N.; Kutygin R.V. (2021)
The paper presents the first detailed evidence for the Permian and Early Triassic ichnofossils of the Southern Verkhoyansk Region. The possibility of using ichnofossils for reconstruction of terrigenous sedimentation at high latitudes, including environments related to the events of the great Permian mass extinction, was discussed. The results obtained are based on ichnofacial and ichnotextural analyses of about 600 samples collected in 2019 from the Tiryakh-Kobyuma section. We found that the Permian and Triassic sediments of the studied section contain numerous icnofossils attributed to 11 ichnogenera. Four ichnoassemblages were identified. They were referred to two ichnofacies - Zoophycos and Skolithos. The Zoophycos ichnofacies includes two ichnoassemblages: Helmintopsis - Phycosiphon - Zoophycos and the depleted Helmintopsis - Phycosiphon ichnoassemblages. This ichnofacies is confined to well-sorted substrates formed in calm temperately deep-water shelf environments, below the level of storm waves, with reduced oxygen content. The Skolithos ichnofacies includes two ichnoassemblages: Arenicolites - Skolithos and Diplocraterion - Arenicolites. It is characteristic of coastal environments with active hydrody-namics and large inputs of clastic and organic matter. The ichnofacies alternate across the section, reflecting sedimentological changing during the accumulation. The sediments of the lower part of the Nekuchan For-mation, corresponding to the Permian mass extinction event, accumulated in calm conditions of a relatively deep shelf. This interval is characterized by the Zoophycos ichnofacies with a depleted Helmintopsis - Phy-cosiphon ichnoassemblage. The depletion of ichnoassemblage and absence of benthic fossils in this part of the section may be caused by anoxic conditions at the basin bottom. The reconstruction of the Permian and Early Triassic environments agrees well with the results of previous studies based on sedimentological and biofacies data.